(untitled) (Modern education and development, 2025)
In the era of rapid digital transformation, online retail provides consumers with fast and convenient services. This article explores the principles of developing a modern inventory and delivery system for online stores based on cloud technologies. It highlights key aspects such as inventory control, real-time monitoring, and automated order management. The use of cloud services such as Amazon Web Services (AWS) and Google Cloud Platform (GCP) to improve system efficiency is analyzed. The proposed solutions are suitable for small and medium-sized businesses, offering cost reduction and faster customer response times.